2018
DOI: 10.3390/ijerph15030456
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Workforce of International University Student Workers: Injury Experience in an Australian University

Abstract: International university students are a growing section of the workforce and are thought to be at greater risk of injury. Qualitative studies have highlighted vulnerabilities, but there is a shortage of quantitative research exploring the injury experience and associated risk factors of this emerging issue. In this study, a total of 466 university student workers across a range of study programs in a single Australian university completed an online survey, with questions relating to their background, working e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Hossain et al [19] found that formal training and encouragement are equally important in leadership. Accidents in the workplace are caused by a lack of safety training, a failure to practice learnt safety instruction, and a lack of confidence in discussing safety issues such as reporting dangers, injuries, or symptoms [8]. As a result, leaders should conduct training on a regular and ongoing basis, especially in the presence of new methods and equipment [18,55,[57][58][59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hossain et al [19] found that formal training and encouragement are equally important in leadership. Accidents in the workplace are caused by a lack of safety training, a failure to practice learnt safety instruction, and a lack of confidence in discussing safety issues such as reporting dangers, injuries, or symptoms [8]. As a result, leaders should conduct training on a regular and ongoing basis, especially in the presence of new methods and equipment [18,55,[57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…According to Guerin et al [6], an estimated 3.2 million non-fatal injuries occurred among young workers (aged 15-24 years) during 2012-2018. This matter is due to their limits in applying what they learn, a lack of experience, and a lack of confidence in discussing safety issues such as reporting hazards, injuries, or symptoms [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…International students can be characterized as young migrant workers [5]. As such, they frequently undertake jobs in the workplace that rank low in terms of employment status and skills [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…To identify factors affecting the risk-taking behaviour of workers, several studies have investigated the reasons why they conduct such behaviour [8,9,10,11,12,13]. Factors influencing the risk-taking propensity of workers include safety supervision and inspection, safety culture of working environments, social influence, workplace conditions, attitude of workers towards risk, risk perception, and self-perceived easiness of risk-taking behaviour [8,9].…”
mentioning
confidence: 99%
“…Tong et al [12] explore human risk factors affecting risk-taking behaviour through coal mining roof accidents in China; such factors include knowledge, information, communication, and performance and behaviour of senior managers. Thamrin et al [13] identify inadequate safety training, long working hours (more than 20 h per week), and insufficient confidence on the discussion of safety issues as the main factors resulting in injuries. Therefore, the awareness and consciousness on occupational safety and health should be enhanced by improving these identified areas to avoid performing unsafe behaviour that will adversely affect the physical and mental health of workers.…”
mentioning
confidence: 99%